Unutterable shame/unuttered guilt : semantics, aporia, & the possibility of Mabo - D. Manderson (Law Text Culture, 1998)
We are a society in which causation-what we do-is understood as deriving from individual action. But in fact our identity-who we are-is plural. The failure to recognise the productive aporia inherent in this relation has seriously confused the debate on Australian history in the wake of, indeed more accurately in the shadow of, terra nullius. In this essay, I want to distinguish between guilt and shame as responses to the past and to insist on the importance of the latter, to demonstrate the paradox within the concept of shame itself, and to argue that the tension between opposites which it contains is in fact a force for beneficial social change.